Sciatic nerve injury associated with acetabular fracture (About a case) - MJEl Mekkaoui; J Boukhris; M Boussaidane; B Chafry; D Bencheba; AS Bouabid; M Boussouga (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Sciatic nerve injuries associated with acetabular fractures is a serious and rare complication. It may be a result of the initial trauma or injury at the time of surgical reconstruction. Prevention requires attention to intraoperative limb positioning, retractor placement, and instrumentation. Patients may present with a broad range of symptoms ranging from radiculopathy to foot drop and the neurological lesions may be irreversible.  We report the case of a 38 years old young man, operated for a left fracture-dislocation of the hip joint complicated by a total paralysis of the sciatic nerve after the surgical act. The diagnosis of the sciatic nerve injury was suspected clinically and confirmed by the electrophysiological explorations. The tomodensitometry was normal without compressive haematoma. After one year of surgery, the patient had a complete recovery of the posterior tibial nerve, and partial recovery of the fibular nerve. The purpose of the clinical case is to account for the need for clinical awareness in the early postoperative period, for early management and improvement of functional prognosis.